Uniform estimates for monotone approximation - Listopad, V. V.; Листопад, В. В.; Листопад, В. В. (Institute of Mathematics, NAS of Ukraine, 1993)
Uniform estimates are obtained for the monotone approximation of the functions from the generalized Babenko classes.